Effect of Teacher’s Quality on Academic Performance of Pupils in Private Secondary Schools in Hargeisa District, Somaliland - Aden, Ahmed; Ajibola, Akeem (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This study was investigating the effect of teacher’s quality on academic performance of pupils in private secondary schools in Hargeisa districts; Teacher qualifications were operationalized as pedagogical processes, knowledge of subject of matter and teacher’s attitudes.The study a risen issue from declined performance of pupils were well demonstrated in study. An increasing the failure of students in recently years from 2018-2022; there was an increase of 6.1% in “D” grades which that reflect an increase of failure students in private secondary schools. Therefore; in this study investigated how take part or effect teacher’s quality on academic performance of pupils in private secondary schools in Hargeisa districts. In additionally the research design was used in this study was a cross-sectional study because it was quick and relatively simple to conducted, also the sample sized collected from information were sample of 169 teacher includes principles and sample of 80 student’s record mid-term examination from private secondary schools in Hargeisa districts. In this study found that; teacher qualification; F( 2,166 )= 3.06;P = 0.00, Pedagogical process; F (2, 166) =3.06 ;P=.002, Knowledge of subject matter; F( 2,166) =3.06, P = 0.002 and teacher’s attitude; F (2, 166) = 3.06; P = 0.001.Such that in those factors are statistical significance which that mean they affect the academic performance of pupils in private secondary schools in Hargeisa districts. By identifying and understanding the key factors influencing on academic performance of pupils in private secondary schools in Hargeisa.In particularly those factors teacher qualifications pedagogical processes, knowledge of subject of matter and teacher’s attitudes.